Advancements in Human Skin Models: From Basic Constructs to Disease-Specific Platforms for Drug Discovery and Therapeutics - Kumar Yadav, Pradeep; Thomas, Steffi; Chandra, Aayush; Kumari Saw, Shweta; Guman, Guman; Kumar Sahu, Jayvant; Kumar, Rajneesh; Kaushal, Sukriti; Sonwani, Hari Prasad (Journal of Neonatal Surgery, 2025)
Skin serves as a major barrier to protect the body from physical, chemical, and pathological risks as well as adjust the transportation of two-way ions and nutrients. To improve the structure and function of skin as well as skin diseases, animal experience is often used, but the difference between surgery and physiology can cause poor animal data in clinical situations. In vitro, models such as the rebuilt epidermis of humans or the equivalent skin are valuable alternatives for animal experiments. There is now a greater demand for alternative in vitro platforms that replicate the structural and functional characteristics of natural skin due to ethical issues and genetic variations in traditional animal investigations. In vitro skin modelling has advanced significantly in recent decades; however, to replicate the pathological characteristics of diseased human skin, distinct repeatable bio-fabrication techniques are needed in comparison to those employed for healthy-skin models, the structural and functional features of healthy human skin to explain human skin modelling with disease markers. detail on how to replicate diseased human skin models in vitro, such as models for atopic, diabetic, skin-cancer, injured, and other pathological skin types. an outlook on diseased‑skin modelling and its technical perspective for the further development of skin engineering.